An analysis of the relationship between the linear hammer speed and the thrower applied forces during the hammer throw for male and female throwers - Brice, S. M.; Ness, K. F.; Rosemond, D. (Sports Biomechanics, 2011)
The purpose of this study was to investigate the relationship between the cable force and linear hammer speed in the hammer throw and to identify how the magnitude and direction of the cable force affects the fluctuations in linear hammer speed. Five male (height: 1.88 ± 0.06 m; body mass: 106.23 ± 4.83 kg) and five female (height: 1.69 ± 0.05 m; body mass: 101.60 ± 20.92 kg) throwers participated and were required to perform 10 throws each. The hammer's linear velocity and the cable force and its tangential component were calculated via hammer head positional data. As expected, a strong correlation was observed between decreases in the linear hammer speed and decreases in the cable force (normalised for hammer weight). A strong correlation was also found to exist between the angle by which the cable force lags the radius of rotation at its maximum (when tangential force is at its most negative) and the size of the decreases in hammer speed. These findings indicate that the most effective way to minimise the effect of the negative tangential force is to reduce the size of the lag angle.